A Highly Efficient Dual-Band Transmitarray Antenna Using Cross and Square Rings Elements - Zhang, Yongliang; Lv, Xiuzhu; Han, Jiaxuan; Bao, Shuai; Cai, Yao; Wu, Zhao (Applied Computational Electromagnetics Society Journal (ACES), 2021)
In this paper, a highly efficient dual-band transmitarray antenna using cross and square rings elements is presented for X and Ku bands. The dual-band transmitarray is designed for downlink/uplink frequencies of Ku band satellite communications. The transmitarray element consists of four metal patches and two dielectric substrates. The metal patch is printed on both sides of the substrate. By optimizing the parameters, the transmitarray element can achieve a transmission phase coverage greater than 360° and work independently in both frequency bands. Then, a method to select the size of the element is proposed, so that all the elements in the array can realize the transmission phase of the two frequencies as much as possible. A 201-elements transmitarray antenna is fabricated and measured and the band ratio of the antenna is 1.13. The measured maximum gain at 11.5 GHz is 22.4 dB, corresponding to the aperture efficiency is 52.7%. The measured maximum gain at 13 GHz is 24.2 dB, corresponding to the aperture efficiency is 62.4%. The 1-dB gain bandwidths are 9.7% (10.8-11.9 GHz) at X band and 9% (12.6-13.8 GHz) at Ku band.